A Qualitative Study: Philosophical Analysis Of A Teacher's Educational Actions - Tuti Azizah; Hashunatulmar’ah Hubwatullah (Jurnal Kajian Ilmu Pendidikan (JKIP), 2026)
The act of educating a teacher is an educational issue that relates to philosophical foundations. The philosophy of educating is about interpreting the task of educating, the purpose, and the essence of education itself for a teacher. Therefore, this philosophy of educating must be well understood by educators, especially teachers. This article explores deeper into the philosophical foundations of a teacher's education and how it affects teachers’ professionalism. The study used a qualitative approach with interviews as a main data collection method. We interviewed 5 junior high school teachers. Findings indicate that the longer a teacher's teaching experience, the more they value education and consider being a teacher as part of their identity. Teachers who have a philosophical foundation in teaching show good professionalism. This philosophical meaning of educating from a teacher will foster educational awareness, aimed at saving educational purpose itself so that it runs as it should – humanizing humans.